A Comparative Study of Breastfeeding Practices Among Working and Non-Working Women Attending a Tertiary Care Hospital, Mysuru - Polineni, Vindhya; Boralingiah, Prakash; Kulkarni, Praveen; Manjunath, Renuka (National Journal of Community Medicine, 2016)
Introduction: Breastfeeding plays a very important role in determining the growth and development of the infant. Considering women’s empowerment, increased women workforce in India, this study was conducted with the objective of comparing infant feeding practices among working and non-working women. Methods: The present study is a hospital based cross-sectional comparative study using purposive sampling with a sample size of 214, 107 in each arm of working and non-working mothers of the children aged between 13-24 months, attending the immunization centre of the Paediatric Medicine department in JSS Hospital, Mysuru from January 2014 to December 2014. Results: Majority among both the groups were found to be below 25 years of age. 53.3% of the non-working and 42.1% of the working women had initiated breastfeeding within one hour of birth. 95.3% of non-working women and 97.2% of the working women had fed their children with colostrum. Conclusion: Exclusive breastfeeding rate was quite higher among the non-working group compared to the working group of women. Mother’s education, socio-economic status, type of family, type of delivery, birth order were the factors found to have influence on breastfeeding practices in the present study.